Correlation of LINE-1 Hypomethylation With Size and Pathologic Extent of Dysplasia in Colorectal Tubular Adenomas. Issue 6 (1st June 2021) - Jiang, Alice C.; Buckingham, Lela; Bishehsari, Faraz; Sutherland, Stephanie; Ma, Karen; Melson, Joshua E.
Abstract : INTRODUCTION: Conventional adenomas (tubular adenoma [TA] or tubulovillous adenoma) and sessile serrated lesions (SSLs) are neoplastic precancerous lesions frequently detected in patients undergoing average risk screening colonoscopy and polyp surveillance. Metachronous risk stratification of adenomas is currently limited to histologic features and size of polyps. We report long interspersed nucleotide element-1 (LINE-1) methylation levels in SSL in comparison to TA and the impact of TA size and presence of high-grade dysplasia (HGD) on LINE-1 methylation. METHODS: LINE-1 methylation was assessed by pyrosequencing of bisulfite-converted DNA. We compared LINE-1 methylation between TA and SSL, among varying sizes of TA, and between TA with HGD and low-grade dysplasia (LGD). RESULTS: LINE-1 methylation declined with increasing polyp size in TA when comparing those <5 mm (72.31 ± 6.11), 5 to <10 mm (67.50 ± 7.00), and ≥10 mm (66.75 ± 11.89). There were lower LINE-1 methylation levels in TA with LGD (n = 119) compared with SSLs (n = 29) (69.11 ± 8.62 vs 81.41 ± 2.43, P < 0.001). TA containing HGD (n = 26) had lower LINE-1 methylation levels than those with LGD (n = 119) (59.86 ± 7.93 vs 69.11 ± 8.62, P < 0.001). DISCUSSION: HGD and increasing size of TA/tubulovillous adenoma were associated with lower LINE-1 methylation. This supports a hypothesis that LINE-1 hypomethylation in TAs indicates advancement along the CRC tumorigenesis pathway. Lower LINE-1 methylation and greater variance of global DNA methylation was seen in TA compared with SSL. LINE-1 methylation in adenomas correlates with polyp size and degree of dysplasia and deserves further study as a predictor of metachronous colorectal cancer risk.